THE EFFECT OF ADDITION CURCUMA’S (Curcuma Xanthorrhiza Roxb) EXTRACT TO THE INCREASE OF FEED CONSUMPTION, EFFICIENCY AND THE GROWTH OF CATFISH (Pangasius) - Prastito Prastito; Pinandoyo Pinandoyo; Ristiawan Agung Nugroho; Vivi Endar Herawati (Jurusan Perikanan dan Kelautan, 2018)
Catfish (Pangasius sp.) Is one of the most cultivated freshwater fish, because it is one of the fish that has a high economic value. However, the use of phytopharmaca is used to improve feed efficiency and fish growth. One of the phytopharmaca which can be used as an antimicrobial is temulawak (Curcuma xanthorrhiza Roxb). This study aims to determine the optimal dose of the effect of temulawak extract on artificial feed in increasing feed consumption, efficiency of feed utilization, and growth rate of catfish (Pangasius sp.). The test fish is maintained with a stocking density of 1 tail / l with a maintenance time of 42 days. This study used an experimental method with 4 treatments and 3 replications. The treatments in this study were Treatment A (addition of 0 ml ginger extract), B (addition of 6 ml temulawak extract), C (addition of 12 ml curcuma extract), and D (addition of 18 ml ginger extract). The data observed included absolute weight, crime scene, EPP, SGR, REP, SR and water quality. The results showed that the addition of temulawak extract to artificial feed had a very significant effect on absolute weights, crime scenes, EPP, SGR, REP but did not differ significantly for survival. The optimum dose of addition of curcuma extract to total feed consumption is 11 ml capable of producing a maximum crime scene of 168.1 g, efﬁciency of feed utilization is 10.5 ml capable of producing a maximum EPP of 70.3% and specific growth rate is 10.8 ml resulting in maximum SGR 2.46% / day